2009
DOI: 10.1007/s00394-009-0086-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between food and nutrient intakes and cognitive capacity in a group of institutionalized elderly people

Abstract: In general, the subjects of our study showed an adequate mental capacity, but those who made no errors in the SPMSQ test had more satisfactory diets. This shows the importance of the diet in the maintenance of cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 26 publications
4
45
0
Order By: Relevance
“…More frequent consumption of plain rolls was associated with significantly lower ratings of their individual sensory attributes and overall acceptability. Findings from previous research partially confirmed our results, showing that repeated consumption of a food generated a decrease in intake and/or in liking of that food (33). However, the study conducted by Touyarou et al (28) confirmed that repeated consumption of a large quantity of bread did not discourage eating bread.…”
Section: Cereal Foods World / 63supporting
confidence: 76%
See 3 more Smart Citations
“…More frequent consumption of plain rolls was associated with significantly lower ratings of their individual sensory attributes and overall acceptability. Findings from previous research partially confirmed our results, showing that repeated consumption of a food generated a decrease in intake and/or in liking of that food (33). However, the study conducted by Touyarou et al (28) confirmed that repeated consumption of a large quantity of bread did not discourage eating bread.…”
Section: Cereal Foods World / 63supporting
confidence: 76%
“…Both dietary and total riboflavin intakes in subjects diagnosed with MCI and Alzheimer's disease were associated with a number of cognitive measures (101,102). Better cognitive functioning in institutionalized elderly individuals in Madrid, Spain, and lower odds of cognitive decline were associated with adequate intakes of vitamins B 6 , B 12 , and riboflavin (33,45). In contrast, lifelong riboflavin intake in a Scottish cohort was not related to cognitive functioning at age 70 (103).…”
Section: Riboflavinmentioning
confidence: 87%
See 2 more Smart Citations
“…Institutionalized elderly Spanish subjects (N = 178) with higher cereal and dietary fiber intakes had fewer errors on memory tests and showed improved cognition (76). The results of a statewide survey of elderly adults in Alabama (n = 1,056) showed bread/cereal intake was inversely associated with cognitive impairment, whereas dessert intake was positively associated with cognitive impairment (77).…”
Section: Breads and Cerealsmentioning
confidence: 99%